Application of scoring systems with point-of-care ultrasonography for bedside diagnosis of appendicitis - AKOĞLU, HALDUN (ZHEJIANG UNIV SCH MEDICINE, 2016)
BACKGROUND: Appendicitis is a common disease requiring surgery. Bedside ultrasound (BUS) is a core technique for emergency medicine (EM). The Alvarado score is a well-studied diagnostic tool for appendicitis. This study aimed to investigate the relationship between patients' symptoms, Alvarado score and ultrasound (US) findings, as performed by emergency physicians (EPs) and radiologists, of patients with suspected appendicitis. METHODS: Three EM specialists underwent the BUS course and core course for appendicitis assessment. Patients suspected of having appendicitis were selected and their Alvarado and modified (m) Alvarado scores calculated. The specialists performed the BUS. Then, patients were given a formal US and surgery consultation if necessary. Preliminary diagnoses, admission or discharge from the emergency department (ED) and final diagnosis were documented. The patients were also followed up after discharge from the hospital. RESULTS: The determined cut-off value was 2 for Alvarado and 3 for mAlvarado scores. The sensitivities of the two scores were 100%. Each score was used to rule out appendicitis. The results of EP-performed BUS were as follows: accuracy 70%, sensitivity 0.733, specificity 0.673, + LR 2.24, and LR 0.40 (95%CI). Radiologists were better than EPs at diagnosing appendicitis and radiologists and EPs were equally strong at ruling out appendicitis by US. When US was combined with Alvarado and mAlvarado scores, EP US+Alvarado/mAlvarado scores <= 3 and radiology US+Alvarado/mAlvarado scores <= 4 perfectly ruled out appendicitis. CONCLUSION: BUS performed by EPs is moderately useful in detecting appendicitis. Combined with scoring systems, BUS may be a perfect tool for ruling out decisions in EDs.
Keywords: Bedside ultrasound; Alvarado score; Appendicitis; DETECT ACUTE APPENDICITIS; SUSPECTED APPENDICITIS; COMPUTED-TOMOGRAPHY; NEGATIVE APPENDECTOMY; ALVARADO SCORE; ULTRASOUND; CT; CHILDREN; US; ACCURACY